Relative income and financial satisfaction across the lifespan - Strother, Benjamin Daniel (Kansas State University, 2020)
What is the relationship between change in financial situation over the lifespan and later life stage financial satisfaction? Framed within the Relative Income Hypothesis, this dissertation investigates the impact of personal background distinctions and lifetime financial change upon financial satisfaction for respondents near or at retirement age. Using the Wisconsin Longitudinal Study, financial satisfaction is measured against changes in income, comparison of financial situation to a reciprocal friend, and present absolute income and net worth using ordinal logistic regression analysis. Relative income effects, measured through longitudinal change from past personal experience (Easterlin approach) and relational standing in society (Duesenberry approach), may offer relevant evidence linking economic origin and comparison feelings regarding a reciprocal friend to financial satisfaction for those at or nearing retirement age. Results suggest that relative income is, at least to some extent, a determinant of financial satisfaction. Downward financial change is correlated with lower financial satisfaction levels. However, evidence does not suggest upward financial change to be correlated to higher financial satisfaction levels. Peer comparison effects do exist, as do absolute income effects in the cross-section. The findings from this dissertation suggest that financial comparison has the power to negatively affect financial satisfaction. In support of the Relative Income Hypothesis, these results encourage a holistic approach to financial planning that appropriately assimilates personal background distinctions and socioeconomic comparison and transition as noteworthy elements of personal financial planning. This dissertation specifically supports the importance of establishing objective and measurable client financial goals, moving clients away from relative income comparisons which lead to lower reported financial satisfaction. The financial planning community can use these findings to incorporate financial background, financial change, and relative social standing into practice as they influence money relationship, money scripts, financial objectives and financial realities of clientele.
Keywords: Relative income; Financial satisfaction; Financial change; Financial planning; Retirement